Activities of the National Defence of Lithuania “Iron Wolf” Kaunas’ Group, 1927–1930 - Petronis, Vytautas (History / Istorija, 2022)
Abstract. The article reviews the activities of the “Iron Wolf” of the Lithuanian National Guard in 1927–1930. The main focus is on the Kaunas group of this organization, reviewing the activities of opposition organizations, the tracking of public institution employees and the formation of nationalist organizations and a bureaucratic apparatus loyal to the nationalists (tautininkai). Based on the archival material, which has so far been little systematically used in the scientific literature, the efforts of the post-coup regime of A. Smetona and A. Voldemaras to establish themselves in power are revealed.